ANTI-INFLAMMATORY AND ANTIARTHRITIC POTENTIAL OF AMMANIA BACCIFERA LINN - S.TRIPATHY; D.PRADHAN; M.ANJANA (International Journal of Pharma and Bio Sciences, 2010)
The anti arthritic potential of Ammania baccifera Linn (Lythraceae) extracts were evaluated by taking chronic inflammatory models like cotton pallet induced granuloma and complete Freund’s Adjuvant (CFA)induced arthritis in albino rats. Arthritis was induced by injecting 0.1ml of complete Freund’s adjuvant below the plantar aponeurosis of the right hind paw. Treatment with the extracts and standard started on the day of induction of inflamogens and continue up to 28 days. In this study both the alcoholic and aqueous extracts significantly (p<0.01) decrease the paw edema on 28th day. The extracts also significantly rectified the deranged hematological parameters. In cotton pallet granuloma inflammation was induced by implanting the sterilized pre weighed cotton pallet subcutaneous in the ventral region of the groin. Treatment continued up to 8 day. The decrease in weight of the cotton pallet as compared to the control was considered as anti-inflammatory effect of the extracts. In both the inflammatory models alcoholic extracts show more potency then the aqueous extracts in terms of percentage of inhibition of inflammation.